'Ritual as erotic anagogy in Pseudo-Dionysius: a Reformed critique'. Issue 3 (27th May 2018) - Darley, Alan Philip
ABSTRACT: Martin Luther famously denounced Pseudo-Dionysius as 'downright dangerous; he Platonizes more than he Christianizes.' In this 500th year of the Reformation I critically examine Luther's judgement firstly by exploring the Neoplatonic background to ritual in Dionysius, secondly by presenting a Reformed critique of this background and finally by arguing for a distinctively Christian Dionysius who survives this critique.